Review of deviations in the" Sherastan" based on the pattern Leech - Abdollah Hasanzade mirali; Mohammad Rezaei; Narjes Moghimi (مطالعات زبانی و بلاغی)
One of the effective ways of highlighting deviations in language and familiar tool that has many applications in poetry .Contact the effect, expanded the meaning of the text and therefore the production of literary pleasure. Contemporary Iranian poetry, especially in recent times with the use of deviations in different ways, in different works of beauty and creating a harmonious society is emerging with different structures. This study aims to describe the analytical methods in constructivist school and the deviation of the eight species Leech's deviations in Sherastan